Attitude and knowledge on oil palm farm biodiversity and willingness to participate in sustainable palm oil certification among oil palm smallholders in Felda Lurah Bilut, Pahang - Gimin, Akram (2016)
Deforestation due to rapid expansion of oil palm cultivation area and other environmental issues related to oil palm productions had caused concern among the public and the NGOs. This led to the establishment of sustainable palm oil certification. Certified sustainable palm oil is palm oil that has been grown on a plantation that has been managed sustainably and certified by the certification body. The objectives of the study are to assess smallholders’ attitude and knowledge on farmland biodiversity and to assess smallholders’ attitude and willingness to participate in palm oil certification scheme. Qualitative and quantitative data were collecting using structured interview with 50 respondents, which were organized smallholders in FELDA Lurah Bilut, Pahang, using convenience sampling. From this study, it show that most of the respondents were lack of knowledge on oil palm biodiversity based on the question asked about wildlife sighting in oil palm farm. Wildlife identified were mostly pests animals and can be hunted for exotic meat. But, most of them concerned on caring these wildlife because of their role in oil palm farmlands. The study also found that smallholders were willing to participate in sustainable palm oil certification and willing to pay on average RM 10 per acre per year. Most respondents agree to the certification requirements pertaining to biodiversity and environmental protection.